Examining the Impact of Academic Supervision, Digital Literacy, and Work Motivation on Teachers’ Pedagogical Competence - Pertiwi, Meilinda Chrisdian; Niron, Maria Dominika (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This research aims to identify: i) the effect of academic supervision on teacher pedagogical competence, ii) the effect of digital literacy on teacher pedagogical competence, iii) the effect of work motivation on teacher pedagogical competence, iv) the effect of academic supervision, digital literacy, and work motivation on teacher pedagogical competence. This research was quantitative research using the survey method. The population was 197 senior high school teachers in Mojoroto Subdistrict and 133 sample was obtained using area proportionate random sampling with the Yamane formula. The results show that: (1) there is an effect of academic supervision on teacher pedagogical competence of 28.5%, (2) there is an effect between digital literacy on teacher pedagogical competence of 58.5%, (3) there is an effect between work motivation on teacher pedagogical competence of 65.5%, (4) there is an effect of academic supervision, digital literacy, and work motivation simultaneously on teacher pedagogical competence of 69.7%. The results of this research can be used as further research with other variables, such as professional competency, teaching method, and others.